Collaborative Practices and Fair Research Uses of Television Archives - Agterberg, Bas; Mustata, Dana (Unlocking Television Archives in the Digital Era. 16th Media Mutations International Conference, 2026)
Academics and television archives have increasingly worked together on platforms and projects over the past twenty years. Prominent examples are EUscreen, launched in 2009, and VIEW Journal of European Television History and Culture since 2012. The archives involved in these platforms are member of the Federation of International Television Archives (FIAT/ IFTA) that was founded in 1977. FIAT/IFTA has over 250 members. Its goal is to promote co-operation amongst radio and television archives, multimedia and audiovisual archives and libraries, and all those engaged in the preservation and exploitation of moving image and recorded sound materials and associated documentation. The Media Studies Commission of FIAT/IFTA encourages academic studies relevant to the development and valorisation of audiovisual archives. It organizes conferences and enables short research projects with a Media Studies Grant. This presentation reflects on the activities of the FIAT/IFTA Media Studies Commission. It looks at previous research commissioned and facilitated through the commission, on topics such as: transnational approaches to television, broadcast anniversaries (2014), the Intervision Songcontest (2016) and the channel Europe Television (2018), the position or representation of women in media, (regional) archives and audiences and post-or decolonial approaches to audiovisual archives. By doing so, this presentation looks at collaborations between academics and archives and the research that emerges at the intersection between these two professional fields. What role do issues related to access to audiovisual heritage or differences between archives play in enabling media research? What are essential ingredients for a fruitful cooperation between archives and academics?